DEVELOPMENT OF COLLABORATIVE MANAGEMENT PLAN FOR UNDERUTILIZED FRUIT TREES (UFT) IN WEST JAVA - Fikry Pratama, Mochammad
Local fruits have been an important part of ecosystems and socio-cultural systems of many communities all over the world for a long time and have a huge potential as alternative food sources and other uses. Nevertheless, the existence of these fruit trees has decreased with the shifting of a fruit-based diet in those communities from local to popular fruits, along with the recurring land conversion. Therefore, the diversity of these underutilized fruit trees (UFTs) become an important part of world plant conservation efforts within the framework of the Global Strategy for Plant Conservation (GSPC) as a derivation of the Convention on Biological Diversity, in which Indonesia is an active member. In the context of West Java, it has been known that at least 49 species of UFTs are dispersed in traditional agroforestry systems (kebun-talun), especially in indigenous land, although these fruits are very difficult to find on the market. This study intends to revive the importance of UFT through a management plan that collaborates stakeholders in West Java Province. Specifically, this study aims to describe species richncess, population, distribution, utilization, and management of UFTs in West Java; to identify stakeholders that have the potential to participate in UFT’s management efforts in West Java and their role; and to formulate a collaborative management plan for the sustainability (in context of population and utilization) of UFTs in West Java. Data was collected through a mix of qualitative and quantitative methods. Lists of fruit tree species were obtained through free-listing interviews, vegetation analysis, and exploratory method in seven indigenous communities in West Java. Interviews were also conducted with some government agencies and private institutions, related to plant diversity and fruit conservation issues to obtain information about their capacity and limitations. Data analysis included identification of UFT condition in West Java, analysis of stakeholder’s role and limitations, and formulation of UFT’s management plan that combines qualitative descriptive analysis, system thinking, and logical framework approach (LFA). A total of 38 species of UFTs can be found in seven indigenous land in West Java with very low populations and utilizations. This also represents the condition of UFTs in typical rural areas of West Java. UFTs are considered to have no economic value, so there is currently no interest among rural people to cultivate and preserve the UFTs. On the other hand, some underutilized fruits (UFs) are sold at very high prices in the urban online markets. Some stakeholders that could potentially be involved in the effort to manage UFTs in West Java are research institution/universities, rural communities, fruit farmers/harvesters, private sector as business driver (through investment and CSR), government agencies, and other parties in West Java as agent of conservation and UFT’s development. Management plan of West Java’s UFT was designed based on the capacity and limitations of the stakeholders. The management plan consists of a few programs that aim to foster community interests, increase the UFT population, and develop the UFT potential so that they could be consumed widely and sustainably.